Ketamine’s double-edged sword: Therapeutic benefits and adverse events in adolescent treatment-resistant OCD - A case series - Suparna Kumar; Jigyansa Ipsita Pattnaik; Udit Kumar Panda; Tanya Dixit; Aashi Srivastava; Shounak Pal; Bhagyashree Acharya; Meghal Gulati; Jayaprakash Russell Ravan (Indian Journal of Psychiatry, 2025)
Background: About one-third of obsessive-compulsive disorder (OCD) cases show poor response to first-line treatments. Ketamine’s role in modulating glutamate, implicated in OCD pathogenesis, warrants investigation. Cases: Four adolescents with treatment-resistant OCD received ketamine infusion (0.5 mg/kg) every other day for six sessions with monitoring using the Children’s Yale-Brown Obsessive Compulsive Scale (C-YBCOS) and Clinician-Administered Dissociative State Scale (CADSS). Three patients showed progressive improvement after multiple infusions with maintained benefits at 2-month follow-up. One patient developed ketamine-induced psychosis. Conclusion: Ketamine shows promise as adjuvant treatment in adolescent OCD, though psychomimetic risks require careful consideration.